457 CD39 Expression in the Glioblastoma Microenvironment does not Affect T Cell Exhaustion or Survival. (April 2023) - Zheng, Allison; Pappu, Ananya; Gill, Sabraj; Stelter, Isabella; Aghi, Manish Kumar
Abstract : INTRODUCTION: Glioblastoma (GBM), the most common malignant brain tumor, is notable for its dysfunctional T-cells. The initial optimism of Immune checkpoint inhibitors has been tempered as these agents have not been successful in treating GBM. CD39 is the first enzyme in the breakdown of ATP to adenosine and is highly upregulated in GBM. CD39 is also thought to contribute to T-cell exhaustion. However, inhibiting the CD39 ATP breakdown pathway did not improve survival in mice, even with PD-1 inhibition, leading to uncertainty about whether non-enzymatic functions of CD39 give it a role in T-cell exhaustion in GBM. METHODS: We performed intracranial injections of SB28 and GL261 GBM cell lines into CD39 global nulls (KO) and C57BL/6J (WT) mice and measured survival. Another cohort of mice were similarly injected and sacrificed after 2 weeks. These tumors were analyzed for T-cell exhaustion markers using flow cytometry. RESULTS: There was no survival benefit seen in either cell line when compared to wild type mice. The immune cell profile was not found to be statistically different between KO and WT mice. Next, expression of known exhaustion markers such as PD-1, TIM3, and LAG3 on tumor infiltrating lymphocytes (TILs) were analyzed. Expression of TIM3 and 2B4 were found to be increased in CD39KO TILs compared to WT (p < 0.01). Additionally, numerous exhaustion markers such as LAG3, TIGIT, and CTLA4 were decreased on TILs compared to peripheral blood T-cells in tumor-bearing mice (p < 0.01). CONCLUSIONS: These results suggest that CD39 lacks a direct impact on GBM outcomes but may affect the expression of other exhaustion markers. Further studies will continue to investigate the interaction between immune checkpoint molecules in GBM.